Hybrid access and adaptive duty cycle clustering protocol for ultra‐low power wireless sensor networks - Adnan Ismail Al‐Sulaifanie; Bayez Khorsheed Al‐Sulaifanie (IET Communications, 2021)
Abstract This paper investigates many drawbacks and limitations of current clustering algorithms designed for wireless sensor networks. These limitations include high resource requirements, significant overhead, tight synchronization requirements, and TDMA limitations. A new clustering algorithm called hybrid access and an adaptive duty cycle clustering (HADC) protocol is introduced, aiming to address the previous limitations. HADC protocol is based on several concepts, including static clusters, adaptive duty cycling, hybrid scheme channel access, minimum node's functionality, and pseudo synchronization. The resulting network's important features are energy efficiency, robustness, low latency, scalability, and self‐healing. The functionality of HADC is validated by both simulation and laboratory experiments. Simulation results show significant improvement of HADC over the well‐known LEACH protocol in terms of energy, latency, and packet delivery ratio. The experiment results show that the node's lifetime with two 3000 mAh batteries and transmitting four packets per minute is about 16 years. The lifetime of the cluster head supported by the same energy sources ranges from 110 to 472 days. HADC is the first clustering algorithm designed for sporadic and low rate WSN applications to the best of authors' knowledge.